2005
DOI: 10.1182/blood-2004-09-3531
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietins can directly activate endothelial cells and neutrophils to promote proinflammatory responses

Abstract: Angiopoietin-1 (Ang1) and -2 (Ang2) are endothelial growth factors that bind to the tyrosine kinase receptor Tie2 and contribute to orchestrate blood vessel formation during angiogenesis. Ang1 mediates vessel maturation and integrity by the recruitment of pericytes. In contrast, Ang2 is classically considered as a Tie2 antagonist, counteracting the stabilizing action of Ang1. Inflammation exists in a mutually dependent association with angiogenesis and we have therefore studied the capacity of angiopoietins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
173
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 45 publications
10
173
1
1
Order By: Relevance
“…It is also possible that the plasma exudates may readily pass the inflamed mucosa and reach the airway lumen through leaky epithelium, thus compromising epithelial integrity and reducing ciliary function and mucus clearance (Foster et al, 1982;Persson, 1996). Although some investigators have described a role for Ang1 in promoting chemotaxis and migration of leukocytes in vitro (Feistritzer et al, 2004;Lemieux et al, 2005), Ang1 has also been shown to reduce leukocyte trafficking in inflammation through the modulation of various inflammatory mediators (Kim et al, 2001;Pizurki et al, 2003;Witzenbichler et al, 2005). Th2 cytokines, adhesion molecules, chemokines, and VEGF play a crucial role in the chemotactic responses for leukocytes, including eosinophils (Wegner et al, 1990;Montefort and Holgate, 1991;Moser et al, 1992;Seder et al, 1992;Foster et al, 1996;Pawankar et al, 1997;Dabbagh et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the plasma exudates may readily pass the inflamed mucosa and reach the airway lumen through leaky epithelium, thus compromising epithelial integrity and reducing ciliary function and mucus clearance (Foster et al, 1982;Persson, 1996). Although some investigators have described a role for Ang1 in promoting chemotaxis and migration of leukocytes in vitro (Feistritzer et al, 2004;Lemieux et al, 2005), Ang1 has also been shown to reduce leukocyte trafficking in inflammation through the modulation of various inflammatory mediators (Kim et al, 2001;Pizurki et al, 2003;Witzenbichler et al, 2005). Th2 cytokines, adhesion molecules, chemokines, and VEGF play a crucial role in the chemotactic responses for leukocytes, including eosinophils (Wegner et al, 1990;Montefort and Holgate, 1991;Moser et al, 1992;Seder et al, 1992;Foster et al, 1996;Pawankar et al, 1997;Dabbagh et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…13 The release of Ang2 resulted in rapid destabilization of the endothelium and triggered an inflammatory response. [13][14][15] A recent study has highlighted Ang2 as having a critical role in animal models of hyperoxia-induced lung injury and inflammation. 12 Ang2 caused increased inflammation and cell death in the lung on exposure to hyperoxia.…”
Section: Introductionmentioning
confidence: 99%
“…8 Arterial stiffness is an important independent predictor of cardiovascular mortality in hypertensive patients, and pulse-wave velocity is a useful index of arterial stiffness and an independent marker of cardiovascular adverse outcome in hypertensives. 9 Finally, eosinophils, 10 neutrophils, 11,12 and a subset of monocytes that contribute to tumor angiogenesis 13 were reported to express Tie-2. In addition, Ang-1 was shown to induce migration of eosinophils 10 and neutrophils, 11 and this is highly relevant because leukocyte migration and invasion into the arterial wall is critical for the development of atherosclerotic lesions and in the development of a vulnerable plaque.…”
mentioning
confidence: 99%
“…9 Finally, eosinophils, 10 neutrophils, 11,12 and a subset of monocytes that contribute to tumor angiogenesis 13 were reported to express Tie-2. In addition, Ang-1 was shown to induce migration of eosinophils 10 and neutrophils, 11 and this is highly relevant because leukocyte migration and invasion into the arterial wall is critical for the development of atherosclerotic lesions and in the development of a vulnerable plaque. 14 In this study, we investigated the expression of Tie-2 on human peripheral blood monocytes and monocyte-derived cell lines and their migratory responses to Ang-1 stimulation.…”
mentioning
confidence: 99%